Improving Cancer Detection and Treatment by pH‐Sensitive Peptide Nanoparticle Drug Delivery Platform: Pharmacokinetics, Toxicity, and Immunogenicity Profile. Issue 3 (30th December 2021) - Choi, Hoon; Cao, Jianbo; Qiao, Hui; Chen, I-Wei; Zhou, Rong
Abstract : It was previously reported that a nanoparticle made of ultra pH‐sensitive peptides (pH‐NP) undergoes self‐dissolution in moderately acidic (pH ≤ 6.9) condition that mimics the pH in extracellular tumor environment, leading to release of drug cargo molecules. Herein, it is demonstrated that this peptide‐based nanodelivery platform can be used to formulate poorly water‐soluble small molecules to improve cancer diagnosis and treatment. Indocyanine green (ICG) encapsulated in pH‐NP (ICG‐pH‐NP) significantly increases tumor‐specific accumulation compared with "free" ICG, leading to excellent in vivo optical imaging contrast. An investigational cancer drug, OTS964, formulated in pH‐NP (OTS‐pH‐NP), sensitizes the drug‐resistant triple‐negative breast cancer to chemotherapy (paclitaxel), resulting in a remarkable tumor regression, whereas OTS964 in standard formulation does not ( P  = 0.0004). The potential immunogenicity and bone marrow toxicity of this nanoparticle are further investigated by administering drug‐free pH‐NP at nanoparticle dose regimens, representing 1.5× and 4.5×, respectively, of which are used in the treatment (OTS‐pH‐NP) study. The data show that the pH‐NP is not immunogenic and is well‐tolerated. Taken together, self‐dissolution and the release of drug cargo in response to the tumor's acidic extracellular pH faciliates drug delivery when mediated by the pH‐NP nano platform, making it a promising, clinical translational delivery platform for enhancing cancer detection and treatment. Abstract : Ultra pH‐sensitive peptide nanoparticle (pH‐NP) undergoes self‐dissolution in a moderately acidic (pH ≤ 6.9) extracellular environment of the tumor, leading to a release of drug cargos to cancer cells. The ability of pH‐NP to improve Indocyanine Green‐based cancer imaging and to dramatically enhance the antitumor effect of a hydrophobic drug (OTS964) is demonstrated along with a favorable safety profile and lack of immunogenicity.